(untitled) (Proceedings of International Conference on Special Education, 2015)
Learning disabilities students (LD) are the group of children who need special attention. Autism (Autistic Spectrum Disorder), Attention Deficit Hyperactivity Disorder (ADHD) and Dyslexia, Dyscalculia and Dysgraphia are included in the group of LD. Community College Management Department (JPKK) is one of the educational institutions in Malaysia that is very concerned on this learning problems. The main purpose of the implementing this program is to give students the skills and knowledge to enable them to adapt to the working environment and to face the real world. A number of programs will be implemented like bakery, culinary, computer, sewing, and photography. Six community colleges were selected to implement the program in their respective colleges. Those colleges are Sungai Siput Community College (KKSS), Bayan Baru Community College (KKBU), Selayang Community College (KKSY), Jelebu Community College (KKJ), Kuching Community College (KKK) and Paya Besar Community College (KKPB). The number of enrollment per session is 10 students with 3M (reading, writing and arithmetic). The main focus of this study is to review the special education program conducted in all the community colleges under the supervision of JPKK. The methodology of the study is distributing questionnaires. Data were collected and analyzed using the Statistical Package for Social Science (SPSS) 17.0. The Cronbach Alpha reliability coefficient of the instrument for lecturers who teaches the LD students is 0.889 and the acceptance of the college citizen is 0.831. This conclude that the skill level of lectures should be improved for them to be more committed and understand the method of teaching and learning of LD students. College infrastructures and curriculum should be revised to provide skills and comfort to the students so they can reap the benefits from this effort. With all these efforts, the JPKK intention to provide knowledge and skills to LD students to become more self-reliant people can be realized.